OP0315 Juvenile idiopathic arthritis patients exhibit persistence in cd4 memory t cells and distinct transcriptomic signature despite biologics therapy. (12th June 2018) - Leong, J.Y.; Yeo, J.G.; Chen, P.; Ally, F.; Chua, C.; Hazirah, S.N.; Lu, P.; Lai, L.; Bathi, L.D.T.; Arkachaisri, T.; Lovell, D.J.; Albani, S.
Abstract : Background: JIA patients respond well to anti-TNFA biologics, with up to 80% of patients achieving clinical remission. In spite of this success, 50%–80% will relapse upon therapy withdrawal, indicating a large proportion of patients had yet to fully resolve their disease. Compounded by concerns with drug toxicities and financial burden, there is a genuine interest to find predictors for successful drug cessation and devise new avenues of therapy. Objectives: To determine how subclinical persistence of disease occurs despite therapy, we compare JIA individuals destined to flare or remain inactive, prior to (To) and after therapy withdrawal (Tend). Previous publications have reveal that CD4 T cells play a vital role in disease pathogenesis in JIA patients. We aim to dissect the CD4 landscape (a) through CyToF, to decipher the CD4 subsets responsible for disease persistence, (b) to unravel the pathways involved through mRNA analysis with Nanostring. Methods: Patients treated with anti-TNF-alpha biologics were recruited with clinically inactive disease on treatment and initiated with therapy discontinuation. The patients designated as flare (n=24) and inactive (n=24) based on 6 JIA core set parameters. Healthy paediatric controls (n=17) with no inflammatory disease were recruited pre-operatively during day surgeries. A separate study with active JIA patients recruited pre/post treatment (n=4 paired) with anti-TNFA biologics and achieving recent clinical remission. Results: Interrogation of PBMCs with CyToF reveal the persistence of a subset of CD3 +CD4+inflammatory memory CD45RA- TNFA +PD1- CTLA4- T cells (p<0.05) in flare (To) versus inactive (To) individuals. Intriguingly an additional subclinical subset, TNFA +IL-6+, was detected (p<0.05) in flare (To) versus healthy individuals. Upon therapy withdrawal, this subclinical subset expands (p<0.05) in flare (Tend) individuals versus inactive (Tend). Notably we also observe a distinct early increase in CD3 +CD4+CD45 RA- CXCR5 +T cells in flare versus inactive (To) individuals which subsides after therapy withdrawal, indicating early T-B interaction. We noted strong but likely inadequate compensatory enrichment of CD45RA- subset of Tregs in flare versus inactive (To/Tend) individuals. To decipher the mechanism that leads to incomplete disease resolution, we sorted CD3 +CD4+CD45 RA- CD45RO+T cells from flare and inactive (To/Tend) patients, and observed striking dysregulation in several major pathways, (a) TCR activation, (b) TNFA signalling, (c) Apoptosis, (d) NF-kB signalling, (e) MAPK signalling. This dysregulation also extends to a separate cohort of active JIA patients naive to anti-TNFA biologics therapy and persisting till recent onset clinical remission. Conclusions: These results highlight a strong immunological memory dysregulation in a subset of CD4 T cells in JIA patients that is predictive of clinical fate and providing new therapeutic insights. Disclosure of Interest: None declared